A Prospective, Split-Face, Randomized Study Comparing a 755-nm Picosecond Laser With and Without Diffractive Lens Array in the Treatment of Melasma in Asians - Woraphong Manuskiatti (2020)
© 2020 Wiley Periodicals LLC Background and Objectives: Treatment of melasma with lasers remains a challenge due to its limited clinical efficacy in addition to high rates of recurrence and side effects. Recently, picosecond lasers have shown favorable results in treatment of benign pigmented lesions. To compare the efficacy and safety of using a 755-nm picosecond laser for the treatment of melasma in a split-face manner, having one side treated with a fractionated beam (diffractive lens array [DLA] coupling) and with a full-beam (flat optics) on the other side. Study Design/Materials and Methods: Eighteen subjects presenting with mixed-type melasma were enrolled. Each patient was randomly treated with a 755-nm picosecond laser coupled with DLA on one side of the face and without DLA (flat optics) on the other side. The laser was delivered through an 8-mm spot size with an average fluence of 0.4 J/cm2 at 2.5 Hz for a total of two passes without pulse overlapping. All subjects received five monthly treatments. Subjective (clinical evaluation) and objective (color readings) assessments on the degree of pigment clearance and adverse effects were obtained at 1-, 3-, and 6-month after the final treatment. Results: At 6 months after the last treatment, physician-rating scores were 1.50 ± 0.76 and 1.50 ± 0.65 of the DLA and flat-optics sides, respectively. Pigment clearance significantly improved from 1 to 6 months after the treatment on each side (P = 0.019 on DLA and P = 0.023 on flat-optics sides). No statistically significant differences in physician-rating scores between the two treatment techniques were observed at all follow-up visits. Objective assessments of melasma clearance corresponded to the clinical evaluation. However, the full-beam (flat optics) provided lower incidence of pos-tinflammatory hyperpigmentation than the fractioned one. Conclusions: A 755-nm picosecond laser is safe and effective for the treatment of melasma in dark-skinned individuals. The use of DLA does not provide additional benefit over the flat optics in clearing pigmentation. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.